Spreading of marine radionuclides through sea spray - Song Yaru; Li Kun; Li Jianlong; Tchinda Narcisse Tsona; Du Lin (National Science Open)
In August 2023, a significant release of radionuclides occurred from the Fukushima Daiichi nuclear power plants, dispersing into the western Pacific Ocean. Sea spray aerosols (SSA) were identified as an important pathway for their atmospheric transport. In this study, an SSA simulation chamber was employed to investigate the enrichment and transport behavior of SSA generated from seawater containing nine different metal ions (Co2+, Ba2+, Mn2+, Sb3+, Cs+, Sr2+, Rh3+, La3+, and Ru3+). Radionuclides showed consistent enrichment with Ca2+, Mg2+, and K+, confirming SSA-mediated transport into the atmosphere. Additionally, the enrichment factor analysis suggested that marine organic matter could enhance the atmospheric emission of metal ions. Trajectory simulations further demonstrated that radionuclide-enriched SSAs can travel long distances, contributing to atmospheric deposition in both marine and terrestrial environments. This study combines experimental and modelling approaches to reveal radionuclides transport via SSAs and provides insights into their environmental impact.